Impact of aberrant DNA methylation patterns including CYP1B1 methylation in adolescents and young adults with acute lymphocytic leukemia. Issue 9 (23rd July 2013) - DiNardo, C.D.; Gharibyan, V.; Yang, H.; Wei, Y.; Pierce, S.; Kantarjian, H.M.; Garcia‐Manero, G.; Rytting, M.
<x xml:space="preserve">Abstract</x> Aberrant promoter DNA methylation is a well‐described mechanism of leukemogenesis within hematologic malignancies, including acute lymphoblastic leukemia (ALL). However, the importance of methylation patterns among the adolescent and young adult (AYA) ALL population has not been well established. DNA methylation of 18 candidate genes in 33 AYA ALL patients was analyzed at diagnosis and during treatment, to evaluate the frequency and clinical relevance of aberrant methylation in an AYA population treated on a uniform therapeutic regimen. Of 16 informative genes, there was a median of 6 methylated genes per AYA ALL patient. Correlations were identified between increasing number of methylated genes with male sex (P = 0.04), increased white blood cell (WBC) count (P = 0.04) and increased bone‐marrow blast percentage (P = 0.04). Increasing age was associated with EPHA5 methylation (P = 0.05). Overall, patients experienced favorable outcomes with median survival that was not reached. On univariate analysis, methylation of CYP1B1 was associated with worse overall survival (HR 10.7, 95% CI 1.3–87.6, P = 0.03), disease‐free survival (HR 3.7, 95% CI 1.1–9.2, P = 0.04) and correlated with decreased CYP1B1 gene expression. A significant incidence of methylation within the AYA ALL population was identified, with increased methylation associated with distinct clinicopathologic features including male gender and elevated WBC count. Our results suggest aberrant methylation among AYA patients is frequent, and may provide a common pathogenic mechanism. The inferior outcome identified with methylation of the cytochrome p450 gene CYP1B1, an enzyme involved in drug metabolism and steroid synthesis, warrants further investigation. Am. J. Hematol. 88:784–789, 2013. © 2013 Wiley Periodicals, Inc.